2018
DOI: 10.1002/slct.201802278
|View full text |Cite
|
Sign up to set email alerts
|

Copper‐Catalyzed Coupling Reactions of Aryl Halides and Phenols by 4,4’‐Dimethoxy‐2,2’‐bipyridine and 4,7‐Dimethoxy‐1,10‐phenanthroline

Abstract: Several Cu(I) complexes of 2,2'-bipyridines were studied for the catalytic coupling of aryl iodides and phenols and 4,4'dimethoxy-2,2'-bipyridine was shown to be an effective ligand of CuI in 1:2 (CuI:ligand) ratio for the synthesis of a wide range of diaryl ethers (up to 97% yield) using K 3 PO 4 as base in DMF at 100°C. The catalysis was highly dependent on the reaction temperature and was successfully applied in the coupling with more attractive and challenging substrates, aryl bromides, at 140°C in good-to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 39 publications
(60 reference statements)
0
19
0
Order By: Relevance
“…This reveals that the combination of pyrazole and pyridine moieties as a N2-ligand is highly efficient for the O-arylation reaction. Moreover, new N3-ligands L4-L7 afforded yields comparable to that obtained using L8, which were much higher than that using the simple 2,2′-bipyridine [30]. Therefore, the appropriately arranged three pyridine moieties effectively work for the reaction.…”
Section: Resultsmentioning
confidence: 91%
See 4 more Smart Citations
“…This reveals that the combination of pyrazole and pyridine moieties as a N2-ligand is highly efficient for the O-arylation reaction. Moreover, new N3-ligands L4-L7 afforded yields comparable to that obtained using L8, which were much higher than that using the simple 2,2′-bipyridine [30]. Therefore, the appropriately arranged three pyridine moieties effectively work for the reaction.…”
Section: Resultsmentioning
confidence: 91%
“…To the best of our knowledge, no study has reported the activities of these seven ligands in O-arylation. In order to investigate the potential of the ligands, the arylation of p-cresol with 4iodotoluene was studied at 100 °C in DMSO in the presence of 10 mol% CuI and 10 mol% ligand, which are 50% and 75% lower than the amounts used for several bipyridine derivatives in our previous work, respectively [30]. The results are summarized in Figure 3.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations